Simple and Rapid Molecular Techniques for Identification of Amylose Levels in Rice Varieties - Cheng, Acga; Ismail, Ismanizan; Osman, Mohamad; Hashim, Habibuddin (MDPI, 2012)
The polymorphisms of Waxy (Wx) microsatellite and G-T single-nucleotide polymorphism (SNP) in the Wx gene region were analyzed using simplified techniques in fifteen rice varieties. A rapid and reliable electrophoresis method, MetaPhor agarose gel electrophoresis (MAGE), was effectively employed as an alternative to polyacrylamide gel electrophoresis (PAGE) for separating Wx microsatellite alleles. The amplified products containing the Wx microsatellite ranged from 100 to 130 bp in length. Five Wx microsatellite alleles, namely (CT)10, (CT)11, (CT)16, (CT)17, and (CT)18 were identified. Of these, (CT)11 and (CT)17 were the predominant classes among the tested varieties. All varieties with an apparent amylose content higher than 24% were associated with the shorter repeat alleles; (CT)10 and (CT)11, while varieties with 24% or less amylose were associated with the longer repeat alleles. All varieties with intermediate and high amylose content had the sequence AGGTATA at the 5'-leader intron splice site, while varieties with low amylose content had the sequence AGTTATA. The G-T polymorphism was further verified by the PCR-AccI cleaved amplified polymorphic sequence (CAPS) method, in which only genotypes containing the AGGTATA sequence were cleaved by AccI. Hence, varieties with desirable amylose levels can be developed rapidly using the Wx microsatellite and G-T SNP, along with MAGE.